The Use of Telemedicine and Other Strategies by Registered Dietitians for the Medical Nutrition Therapy of Patients With Inherited Metabolic Disorders During the COVID-19 Pandemic - Singh, Rani H.; Pringle, Theresa; Kenneson, Aileen (Frontiers in Nutrition, 2021)
The clinical management of patients with inherited metabolic disorders (IMDs) includes medical nutrition therapy (MNT) by a registered dietitian (RD). We utilized an online quantitative and qualitative survey to characterize the practices of RDs treating patients with IMDs during the COVID-19 pandemic and to identify challenges and unmet needs. We received responses from 117 RDs. Results indicate that RDs are using alternate methods to engage this vulnerable population and provide MNT during the pandemic, including offering telemedicine appointments. Barriers to implementation of telemedicine include the limitations of virtual visits (inability to conduct physical exams and collect blood samples), time, patient knowledge of technology, audio problems, and patient access to internet, computers, or smartphones. RDs have addressed these barriers by extending prescriptions without a medical exam, relying on local facilities for blood draws, increasing the number of patients that use at-home filter papers for blood monitoring, and expanding the use of phone calls and emails. RDs identified patient education materials to facilitate telemedicine visits as a primary unmet need. Despite the reported barriers and limitations of telemedicine for MNT of IMDs, there was widespread satisfaction with the approach among RDs, with 96.9% reporting that they were somewhat or very satisfied with telemedicine. Although this survey focused on barriers, benefits of telemedicine for both RDs and patients were also reported. Identification of barriers and unmet needs can help clinics plan strategies to maximize telemedicine delivery models, to improve efficiency and patient outcomes, and to support sustained use of telemedicine post-pandemic.